2000
DOI: 10.1126/science.287.5453.622
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube Molecular Wires as Chemical Sensors

Abstract: Chemical sensors based on individual single-walled carbon nanotubes (SWNTs) are demonstrated. Upon exposure to gaseous molecules such as NO(2) or NH(3), the electrical resistance of a semiconducting SWNT is found to dramatically increase or decrease. This serves as the basis for nanotube molecular sensors. The nanotube sensors exhibit a fast response and a substantially higher sensitivity than that of existing solid-state sensors at room temperature. Sensor reversibility is achieved by slow recovery under ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

86
3,530
5
21

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 5,853 publications
(3,642 citation statements)
references
References 23 publications
86
3,530
5
21
Order By: Relevance
“…For example, NO 2 gas acts as a source of acid rain and contributes to the formation of ozone (O 3 ), which is the major cause of photochemical smog 5, 6. NO 2 at a concentration higher than 1 ppm can also cause serious diseases to people's respiratory system 2, 6, 7. Furthermore, ammonia (NH 3 ) is a toxic and colorless gas with permissible exposure limit of 50 ppm over 8 h per working day or 40 h per working week 8.…”
Section: Introductionmentioning
confidence: 99%
“…For example, NO 2 gas acts as a source of acid rain and contributes to the formation of ozone (O 3 ), which is the major cause of photochemical smog 5, 6. NO 2 at a concentration higher than 1 ppm can also cause serious diseases to people's respiratory system 2, 6, 7. Furthermore, ammonia (NH 3 ) is a toxic and colorless gas with permissible exposure limit of 50 ppm over 8 h per working day or 40 h per working week 8.…”
Section: Introductionmentioning
confidence: 99%
“…1 In this letter we concentrate on the possibility of using carbon nanotubes as chemical sensors and probes. Pioneering experiments from Dai's group 2,3 have shown that at room temperature the resistance of an individual single wall carbon nanotube is very responsive to the adsorption of molecules, such as NO 2 and NH 3 . These measurements demonstrate the excellent sensing capabilities of CNTs, in particular their fast response time, high selectivity, and reversibility.…”
mentioning
confidence: 99%
“…Unique mechanical and electronic properties of these molecular-scale wires enabled a variety of applications ranging from novel composite materials, 4 to electronic circuits, 5 to new sensors. 6 Often, these applications require non-covalent modification of carbon nanotubes with organic compounds, 7 DNA and biomolecules, 8 and polymers 9 to change nanotube properties or to add new functionality. We recently demonstrated a versatile and flexible strategy for non-covalent modification of carbon nanotubes using layer-by-layer self-assembly of polyelectrolytes.…”
mentioning
confidence: 99%